Materiality and interior construction - Gesimondo, Nancy; Postell, James Christopher (Hoboken, New Jersey : John Wiley & Son, Inc., 2011)
A comprehensive reference of materials for interior designers and architects. Choosing the right material for the right purpose is a critical$1 (Band often overlooked$1 (Baspect in the larger context of designing buildings and interior spaces. When specified and executed properly, materials support and enhance a project's overall theme, and infuse interior space with a solid foundation that balances visual poetry and functionality. Materiality and Interior Construction imparts essential knowledge on how materials contribute to the construction and fabrication of floors, partitions, ceilings, and millwork, with thorough coverage of the important characteristics and properties of building materials and finishes. Individual coverage of the key characteristics of each material explores the advantages and disadvantages of using specific materials and construction assemblies, while helping readers discover how to make every building element count.s
Preface -- Acknowledgments -- Foreword -- 1. Why materials matter -- 2. Flooring -- 3. Walls, partitions, and vertical components -- 4. Ceilings -- 5. Millwork -- Appendix -- Notes -- Glossary -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: BUILDING MATERIALS